Identification of organic contaminants in vinasse and in soil and groundwater from fertigated sugarcane crop areas using target and suspect screening strategies - da Silva, Josiel José [UNESP]; da Silva, Bianca Ferreira [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Petrović, Mira; Gros, Meritxell; Gago-Ferrero, Pablo (Elsevier, 2021)
This work evaluated for the first time the sustainability of vinasse reuse as a fertilizer in sugarcane crops by assessing the occurrence of organic contaminants and their potential for dissemination to soils and groundwater in fertigated areas. A comprehensive screening of organic contaminants was performed in vinasse, soil and groundwater using target analysis, to investigate the occurrence of multiple-class antibiotics, in combination with suspect screening using NORMAN Digital Sample Freezing Platform. Even though antibiotics are used in the ethanol production process and were expected to be ubiquitous contaminants, they were not detected in any of the samples. Nevertheless, the HRMS-based wide-scope suspect screening (including >7800 substances such as pharmaceuticals, agrochemicals, preservatives and industrial chemicals) allowed the tentative identification of 56 compounds, mostly pesticides, food additives, industrial and naturally occurring substances. Results showed no overlap between the compounds detected in vinasse and environmental samples, suggesting that the pollutants found in soil and groundwater might come from alternative sources other than vinasse reuse.
Keywords: Antibiotics; NORMAN Digital Sample Freezing Platform; Organic contaminants; Soil amendment; Suspect screening; Vinasse fertigation